Torta Alert Manifesto. For the visibilisation of lesbian identities - Alerta Torta (Área Feminismos, Género y Sexualidades del Centro de Investigaciones "María Saleme de Burnichón" de la Facultad de Filosofía y Humanidades, Universidad Nacional de Córdoba, 2021)
Alerta Torta was born as a political space, in a context marked by the multiple urgencies that made up our lesbian existences. Those of us who converged in the formation of Alerta Torta came together around the need to enunciate lesbian voices in a Cordoba that was too hostile to us. voices in a Cordoba that seems too hostile to us, with the aim of making lesbian voices more and more to make the specific demands of lesbian identities more and more audible. The construction of Alerta is the result of a nomadic itinerary, a note that cuts across many of the political political trajectories of many of us, in the search, precisely, for a space of our own. space of our own. The need to make life more livable for ourselves and to rethink the ways in which we respond to the the ways in which we respond to violence towards and among us are central issues in our current debates that are central issues in our current debates, which are combined with the conviction that we need to to chart horizons of collective emancipations with the multiple existences-others that the heteronorma, cisgendered heteronorma, cis-sexist culture, gender oppression and capitalism impose on us. The following pages are intended to be an approximation to these debates and discussions in a narrative approached from the first person plural, from our situated subjectivities and practices. situated and localised subjectivities and practices.